Organizational politics - Rosen, Christopher C. (Henry Stewart Talks, 2012)
Political climate, Perceptions of organizational politics, Political behavior, Political skill, Organizational politics and stress, Transactional model of stress, Conservation of resources theory, Coping activities, Politics and well-being, Stress-related outcomes, Managing politics at work
Reviewed at 2021/02/25